Indigenous Tourism in Nueva Ecija: Challenges and Opportunities - Fernandez, Khriz N. (Future Science / FSH-PH Publications, 2024)
Indigenous tourism played an essential role to help build local and national economy. It served as the spine of every municipality which hold attracting tourism sites. Hence, indigenous tourism as emerging tourism attraction also held a frontier of economic power that help boost local economy. It was concluded that ICCs/IPs encountered certain challenges as to cultural sensitivity, economic stability and environmental preservation which hampered the continued development of indigenous tourism. Meanwhile, the results also showed that in spite of these challenges, opportunities were also seen in which, indigenous tourism provided wider avenues for the development of ICCs/IPs way of living through creation of more employment and business opportunities which helped them generate more income to meet their needs. Conclusively, indigenous tourism in the province empowered ICCs/IPs cultural, environmental and economic opportunities.